The Role of the Constitutional Judiciary’s Interpretative Jurisdiction in Protecting the Economic Identity of the State - Salih, Sarwa Shareef Mohammed; Salman, Fawzi Husein (Journal of Ecohumanism, 2025)
The 2005 Constitution of the Republic of Iraq defines the structure of the state and its system of governance. Although it incorporates the foundations of a democratic political system, including the peaceful transfer of power through elections, guarantees of fundamental rights and freedoms, and the principle of separation of powers, among others, it also contains several contradictions and deficiencies within its political and economic provisions.